Jamaah Islam Eksklusif: Studi terhadap Pola Interaksi Sosial Jamaah LDII Kota Jambi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This research qualitatively describes the existence of Jamaah LDII (The Congregation of The Propagation of Islam in Indones ia) and their interctction patterns, int ernally and externally. For the purpose of this research, the data is taken through depth interviery participant observation and documentation. From the research, it is found that in their social interaction, there are some social interaction patterns they undergo such as cooperation, competition, and even conflict. These patterns occur internally and internally with the surrounding neighbors. Positive social interaction patterns occur internally and negative one occurs to the neighbors, to people out side their group. It is suggested and recommended that both parties organize intent discussion to bridge their gaps for a peace and co-existence among them.